HOW TO DEAL WITH AN ECONOMIC RECESSION FROM HADITH PERSPECTIVE - Prasetyo, Abdullah Alifuddin; Arrohman, Eprom Rijal (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
The economic stability of a country is a core foundation that must be well maintained by its people, also it depends greatly on how its peoples interact with the economy. One of the problems that threatens the economic stability of a country is a recession, an economic problem that every country tries to prevent and avoid. Allah is the All-Provider, He provides humans with sustenance non-stop daily. Allah and His messenger have guided the people through the Al-Qur’an and hadith so that they could deal with economic problems such as a recession. The goal of this research is to examine the definition of recession, its causes, and to convey the solutions to an economic recession from the perspective of hadith. The approach of this research is library research, and the technique for data analysis is content analysis from books, journals, and websites. The results of this study concluded that: (1) Recession is a period of decline in economic activity. (2) The causes of an economic recession are many, such as inflation and an imbalance between production and consumption. (3) There are several solutions to deal with recession from the perspective of hadith.